Het laatste jaar van de klaproos : denkend aan Maurice Coppieters - Verdoodt, Frans-Jos; Gunst, Petra; Seberechts, Frank (Leuven: Van Halewyck; Antwerpen: ADVN, 2009)
"Frans-Jos Verdoodt (ed.), Petra Gunst, Frank Seberechts"